Modulation of wingless signaling by Notch in Drosophila. - Hing, H.K.; Sun, X.; Artavanis-Tsakonas, S. (Mechanisms of Development, 1994)
Extensive genetic and molecular analyses indicate that Notch acts as a transmembrane receptor in an evolutionarily conserved cell interaction mechanism that appears to control a common step in the progression of an uncommitted cell towards the differentiated state. In Drosophila, Notch mutations were shown to affect the development of a broad spectrum of tissues, including the wing. We found that mutations in the segment polarity gene wingless are capable of acting as dominant enhancers of notchoid, a recessive Notch allele affecting the wing. The Wingless protein is homologous to the mammalian proto-oncoprotein Wnt-1 and is thought to act as the signal in a cell interaction mechanism that specifies differentiation of the embryonic epidermis as well as imaginal structures such as the wing. Although some components of the Wingless signal transduction pathway have been identified, the receptor for Wingless remains elusive. This genetic link between the Wingless and Notch pathways has been further examined by determining the relative expression patterns and subcellular localization of Notch and Wingless in mutant and wild-type backgrounds. We find that Notch is necessary for the implementation of the Wingless signal in specifying normal wing development. We discuss the possibility that Notch is directly involved in the reception of Wingless in the light of current models for the developmental action of Notch.